Predictive value of sarcopenic findings in the psoas muscle on CT imaging among patients with sepsis - Okada, Yohei; Kiguchi, Takeyuki; Okada, Asami; Iizuka, Ryoji; Iwami, Taku; Ohtsuru, Shigeru (The American journal of emergency medicine, 2021)
This study aimed to determine the association between sarcopenic findings of the psoas muscle and mortality in patients with sepsis; further, it aimed to assess its clinical utility, in addition to the sequential organ failure assessment (SOFA) score, in predicting mortality. This retrospective single-center cohort study included adult patients with sepsis, who were admitted to the intensive care unit, between January 2012 and December 2018. The cross-sectional area of the psoas muscle at the L3 level was measured using computed tomography (CT) images, following which the subjects were categorized as “Above middle,” “Middle,” and “Sarcopenic.” The association between sarcopenic findings and 90-day mortality was investigated by logistic regression analysis. A “modified SOFA score,” by adding sarcopenic findings to the SOFA score, was developed and evaluated for its predictive performance. Here, 255 patients with sepsis, who were admitted to the intensive care unit (median age, 76 [64–84] years; SOFA score, 9 [5–14]), were included. The adjusted odds ratio for the “Middle” and “Sarcopenic” groups for 90-day mortality was 2.40 (95% confidence interval [CI]: 0.93–6.15) and 3.67 (95% CI: 1.39–9.68), respectively. The c-statistics of the SOFA and modified SOFA score was 0.731 [95% CI: 0.650–0.799] and 0.749 [95% CI: 0.673–0.813]. On decision curve analysis, a little additional net benefit was observed on using the modified SOFA score. The results suggested an association of the sarcopenic findings of the psoas muscle on CT imaging with 90-day mortality; however, the modified SOFA had few additional clinical values to that of SOFA in predicting 90-day mortality. •Sarcopenic findings of psoas muscle on CT imaging were associated with 90-day mortality in adult patients with sepsis.•A dose-response relationship exists between sarcopenic findings and mortality.•Sarcopenic findings have a marginal additional benefit in predicting mortality compared to the SOFA score.